ANALISIS PENGARUH PENGGUNAAN PASSIVE SPLITTER PADA OPTICAL DISTRIBUTION POINT (ODP) TERHADAP KINERJA JARINGAN DI RUMAH PELANGGAN - Ilham Minal Zukri (Jurnal Ilmiah Poli Rekayasa, 2022)
In this study, a comparison was made of the attenuation values ​​of passive splitters 1:8 and 1:16 in Optical Distribution Points (ODP). Perform several measurements at the ODP using an Optical Light Source paired with a Passive Splitter 1:4 and 1:8 to become input power at the Optical Distribution Cabinet (ODC) and measure the output from the Passive Splitter 1:8 and Passive Splitter 1:16 at the ODP using Optical Power Meter (OPM) as a measuring tool with a cable length parameter of 100 meters. The measurement results using the OPM are smaller than the calculations with the Power Link Budget, with the measurement results of the passive splitter 1:8 on ODP with measurements made at the rosette obtained attenuation of -19.78 dBm and the results of measurements on passive splitter 1:16 on ODP with measurements carried out in the rosette the attenuation is -23.57, from these results it can be said that the use of passive splitters with excess needs can be used with replacement of passive splitters that have more capacity.